Ontogenic time and morphometric analysis of in-vitro rearing of stingless bee queen, Heterotrigona itama (Hymenoptera: Apidae: Meliponini) - Wahizatul Afzan Azmi,; Nurul Izdihar Razali,; Nur Azmina Adnan,; Shamsul Bahri Abdul Razak,; Wan Bayani Wan Omar,; Ehsan Abdul Rahman, (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2022)
The incubation period and life cycle of the queen of stingless bee, Heterotrigona itama is poorly understood. Little is known about the growth and development time of H. itama queen during ontogenic development which is the vital key to understanding many aspects of their biology. This study examined the growth rate and ontogenic period of Indo-Malaya stingless bee queens under in-vitro conditions. The mean ontogenic time for queens of H. itama, was maintained at 25+2.5oC and relative humidity 75-100% approximately for 56 days, which is dissimilar to the H. itama workers. The immature stage showed an apparent variation in head capsule width measurement, with the early instar ranging from 0.49±0.07 mm and late instar ranging until 2.83±0.10 mm. Overall, there are five to six instar stages that could be found from this species. Ten morphological characters were measured and compared between in-vitro queens and wild workers of H. itama. The body and abdominal length of in-vitro queens of H. itama were significantly greater than wild workers. However, the wings and legs of H. itama workers were significantly lengthier compared to the in-vitro queens. It is hoped that the outcomes of this study will contribute to conservation efforts in Indo-Malaya stingless bees.